Procedures For Examining Inherited Land in the Perspective of the Basic Agrarian Law (UUPA): Prosedur Nyusuki Tanah Warisan dalam Perspektif Undang-Undang Pokok Agraria (UUPA) - Addini, Yurike; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the procedure for acquiring inherited land in the perspective of the Basic Agrarian Law as well as to find out the legal protection for one of the heirs whose inheritance land is transferred. The research method used by the author is normative law research using a statutory approach or can also be called the Statute Approach. By using primary legal materials, namely legislation related to legal issues in this study. Then secondary legal materials in the form of journals, books, articles and other literature. And the analysis used by the author is the method of deduction. The conclusion of this study is that the procedure for acquiring inherited land in the perspective of the LoGA must be based on a mutual agreement between the rights holders to terminate the joint ownership with evidence of the deed of sharing the joint rights made by PPAT. There are several chronologies of the occurrence of this nyusuki, among others, when there are two heirs, where one heir really needs money, so the other heirs provide access. Then another chronology is when there is one heir who has occupied the land from before the heir dies until he dies, and the heir does not want to sell the land inherited by the heir.